Respuestas

2012-03-11T21:46:05+01:00

{- 5x + 6y = 12 | x (- 2)

{ 7x + 12y = -10

 

{ 10x - 12y = - 24

{ 7x + 12y = -10

----------------------

  17x = - 34 | : 17

  x = -2

 

7x + 12y = -10

7 x (-2) + 12y = -10

-14 + 12y = -10

12y = - 10 + 14

12y = 4 | : 12

y = 4/12

y = 1/3

 

x = - 2

y = 1/3

2012-03-11T22:01:42+01:00

-5x+6y=12

6y-12=5x

(6y-12)/5=x

 

Reemplaza x en la otra ecuación:

 

7x+12y=-10

7((6y-12)/5)+12y=-10

(42/5)y-84/5+12y=-10

(102/5)y=34/5

102y=34

y=34/102=1/3

 

ahora que tienes el valor de y, lo reemplazas en esta fórmula para tener el valor de x:

x=(6y-12)/5

x=(6*1/3-12)/5

x=(2-12)/5=-10/5

x=-2

 

Rpta:

y=1/3

x=-2

 

saludos,

 

ARPA